PENINGKATAN KEMAMPUAN ANAK USIA DINI MENGENAL ANGKA 1-10 MELALUI MEDIA TUTUP BOTOL DI TK PERTIWI PALATIHAN - Nur Istito'ati; Winda Oktaviana (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Caps at TK Pertiwi, Pelatihan. There are 7% of children in kindergartens, training has not been able to recognize numbers, 2% of children are starting to know numbers because teachers use classic methods so that children feel bored. This research praise is to improve the numerical ability of children in Pertiwi Kindergarten, Training. The purpose of this research is to improve the ability to recognize the numbers 1-10 through the media of bottle caps in Pertiwi Kindergarten training. The research method used is classroom action research. The research in this class was carried out in two cycles. Each cycle consists of four steps: preparation, implementation, evaluation, and reflection. The results of the study show that children's ability to recognize the numbers 1-10 can be improved by using bottle cap media. The improvement in the ability to recognize the numbers 1-10 was seen during the transition from cycle I to cycle II. Four children (or 34% of the total children) in the first cycle achieved the success indicator. The number of children increased to nine children in the second cycle, or 75%